2008
DOI: 10.1007/s00330-008-1060-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-fluid levels in bone neoplasms: variation of T1-weighted signal intensity of the superior to inferior layers—diagnostic significance on magnetic resonance imaging

Abstract: The diagnostic relevance of the relative T1-weighted (T1W) and T2-weighted (T2W)/short tau inversion recovery (STIR) MRI signal intensity characteristics of the superior to inferior fluid layers within fluid-fluid levels (FFLs) found in bone tumours was investigated. A retrospective analysis was performed of MRI studies of 2,568 patients presenting with a suspected bone tumour over an 8-year period. Final diagnosis was made by biopsy/surgical resection or characteristic imaging/clinical findings. Subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…In our case there were also fluid-fluid levels (FFLs) in more than half of the mass, an unspecific finding that may occur in a wide range of bone and soft tissue tumors, benign and malignant and non-neoplastic disease [13][14][15][16]. Usually they are related to prior hemorrhage or tumor necrosis [13,14].…”
Section: Discussionmentioning
confidence: 85%
“…In our case there were also fluid-fluid levels (FFLs) in more than half of the mass, an unspecific finding that may occur in a wide range of bone and soft tissue tumors, benign and malignant and non-neoplastic disease [13][14][15][16]. Usually they are related to prior hemorrhage or tumor necrosis [13,14].…”
Section: Discussionmentioning
confidence: 85%
“…There is no dedicated study on the most common etiology of osseous lesions with FFLs in pediatric patients, to our knowledge. In addition, large studies that may have included some pediatric patients had not published their detailed results based on age groups, [5][6][7] and the current literature is mainly limited to published case reports. [9][10][11][12][13][14] There are only 2 case reports describing the presence of fluid-fluid level in LCH.…”
Section: Discussionmentioning
confidence: 99%
“…However, 2 large studies primarily in adult patients have demonstrated that ABCs are the most common etiology of osseous lesions with FFLs throughout the body. 5,6 Despite these data, the presence of FFLs remains a nonspecific finding and can be seen in a wide range of benign and malignant bone lesions, including fibrous dysplasia, telangiectatic osteosarcoma, osteoblastoma, simple bone cyst, lymphatic malformations, Ewing sarcoma, brown tumor, giant cell tumor, and chondroblastoma. [5][6][7][8][9] In this study, head CT and MR imaging of pediatric patients having skull lesions with FFLs were retrospectively reviewed with the aim of characterizing these lesions.…”
mentioning
confidence: 99%
“…CT and MRI reveal FD as diffuse hyperostosis, bony expansion with ground glass appearance, intraosseous cysts, and contrast enhancement [9,13], whereas ABCs are expansile and destructive, containing blood-fluid level lesions [13]. However, the presence of free-fluid levels remains a nonspecific finding and can be seen in a wide range of benign and malignant bone lesions, including cephalohematoma, histiocytosis, telangiectatic osteosarcoma, osteoblastoma, simple bone cyst, lymphatic malformations, Ewing sarcoma, brown tumor, giant cell tumor, leukemia, myelodysplasia syndromes, metastases, non-Hodgkin lymphoma, multiple myeloma, mastocytosis, Paget disease, and chondroblastoma [14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%